PENGARUH KEBIJAKAN DIVIDEN, STRUKTUR MODAL, DAN TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI Periode 2013-2017) - Amelia Monica Ningrum; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the relationship of dividend policy, capital structure and interest rates to firm value. The type of research used is explanatory. The data used is secondary data, obtained by documentation techniques, namely by searching for and collecting annual report data obtained from the website. The population that is the object of this research is companies in the property and real estate sector listed on the Indonesia Stock Exchange in the period 2013-2017, namely as many as 48 companies. The sample selection used a purposive sampling technique, so that 17 companies were obtained.The data analysis techbique in this study used the normality test, classic assumption test, multiple linear regression test and hypothesis test. The measuring instrument used to measure dividend policy is the Dividend Payout Ratio (DPR), for the capital structure using a Debt to Equity Ratio (DER), and to measure interest rates using the BI Rate of Bank Indonesia Certificates (SBI), while measuring instruments are used to measure company value is Price Earning Ratio (PER).The results of data analysis show that: (1) dividend policy has a positive effect on firm value, (2) capital structure has a positive effect on firm value, while (3) interest rates have a negative effect on firm valueKeywords : Dividend Policy, Capital Structure, Interest Rates, and Firm Value.